FIGURATIVE LANGUAGE AND CONTEXTUAL MEANING: IN THOMAS HARDY POEMS - Septa Aryanika; Ayu Anggraini; Nunun Indrasari (Universitas Wiralodra, 2022)
Despite the growing body of research documented the analysis of poem in EFL learning, relatively few of literature examines the representation of figurative language and textual meaning situated in the ELT context. To fill this gap, the objective of figurative language is to enhance a poem's beauty and unique effects by also creating it much more interesting and distinctive. This research goal is to examine the representation of figurative language and contextual meaning in Hardy poems. The poems scrutinized by the researcher were